Webster Street at Ed Rickett's Lab - Peter Stackpole:::Creator::::::::::::
Webster (Toby) Street at Pacific Biological Laboratory, leaning against the railing at Doc Rickettt's Lab, 800 Cannery Row. Note on the back of the photograph: 'Great picture of Toby, taken for Steinbeck Country. Not Used (G. Wilson)....' RESTRICTED USE Original in safe